2014
DOI: 10.3390/nu6083214
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Supplementation in Chemical Colorectal Carcinogenesis: A Two-Edged Knife

Abstract: This work investigated the effects of Vitamin E (VE) on aberrant crypt foci (ACF) incidence, oxidative stress parameters (serum and hepatic VE concentration, and homocysteine, glutathione (GSH), and malondialdehyde (MDA) levels), and expression of both cyclooxygenase-2 (COX2) and proliferating cellular nuclear antigen (PCNA) in experimental colorectal carcinogenesis. Male Wistar rats received subcutaneous injections of 1,2-dimethylhydrazine (DMH) twice a week, for two weeks (40 mg/kg), except for the Control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In a similar study in AOM‐treated male BALB/c mice, however, γ‐T, but not γ‐TmT, (1 g/kg diet) suppressed moderate colitis‐promoted colon tumorigenesis, but neither agent was effective in inhibiting severe colitis and related colon tumorigenesis 105 . Interestingly, in a 1,2‐dimethylhydrazine‐induced colon cancer model in male Wistar rats, supplementation with a low dose of VE (α‐T) (225 IU, 3 times the RDI) had beneficial effects in reducing colon aberrant crypt foci (ACF) formation and COX2 expression, while a high dose of α‐T (1500 IU) did not 106 . A comparative study of the inhibitory activity of α‐T, γ‐T, and δ‐T (at 2 g/kg diet) was conducted in AOM‐treated Fischer 344 rats 107 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 99%
“…In a similar study in AOM‐treated male BALB/c mice, however, γ‐T, but not γ‐TmT, (1 g/kg diet) suppressed moderate colitis‐promoted colon tumorigenesis, but neither agent was effective in inhibiting severe colitis and related colon tumorigenesis 105 . Interestingly, in a 1,2‐dimethylhydrazine‐induced colon cancer model in male Wistar rats, supplementation with a low dose of VE (α‐T) (225 IU, 3 times the RDI) had beneficial effects in reducing colon aberrant crypt foci (ACF) formation and COX2 expression, while a high dose of α‐T (1500 IU) did not 106 . A comparative study of the inhibitory activity of α‐T, γ‐T, and δ‐T (at 2 g/kg diet) was conducted in AOM‐treated Fischer 344 rats 107 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 99%
“…However, when AOM‐initiated carcinogenesis was promoted by relatively mild colitis induced by one cycle of DSS, γ‐T decreased tumor multiplicity demonstrating that γ‐T is able to alleviate moderate but not severe colitis‐promoted tumorigenesis . Administration of different doses of vitamin E in a 1, 2‐dimethylhydrazine induced model of colorectal carcinogenesis in male Wistar rats demonstrated that 1500 IU of vitamin E is hazardous, whereas 225 IU of vitamin E has beneficial effects on colorectal carcinogenesis associated with reduced aberrant crypt foci and decreased cyclooxygenase 2 expression . Investigation of the growth inhibitory effects of different forms of tocopherols, tocopherol phosphates, and tocopherol quinones on human colon cancer cells, HCT116 and HT29, revealed that tocopherol phosphates and tocopherol quinones had higher inhibitory activities than their parent compounds .…”
Section: Experimental Studies With Tocopherolsmentioning
confidence: 99%
“…Thus, the quantification of MDA content indicates the level of destruction of macromolecules as a direct result of lost cellular functions, which can eventually lead to death. 25,26 It has been demonstrated that environmental factors such as hydric stress can severely affect the accumulation of oxygen radicals and MDA in plants. [27][28][29][30] The lab practical presented here involves the 3-day experiment described below, which is aimed at teaching students from the advanced biochemistry course about certain antioxidant mechanisms that plants trigger in order to eliminate the excess generation of ROS produced in cells under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…This damage on cell membrane fatty acids generates small carbonyl compounds, including malondialdehyde (MDA), a cytotoxic product that can be used as a free radical level indicator. Thus, the quantification of MDA content indicates the level of destruction of macromolecules as a direct result of lost cellular functions, which can eventually lead to death 25,26 . It has been demonstrated that environmental factors such as hydric stress can severely affect the accumulation of oxygen radicals and MDA in plants 27–30 …”
Section: Introductionmentioning
confidence: 99%